Kualitas Sensori Snack Bar dengan Perbedaan Proporsi Kelapa Parut dan Pindang Ikan Tongkol (Euthynnus Affinis) - Pamela Daffa Aliftia Siregar; Lilis Sulandari; Asrul Bahar; Ila Huda Puspita Dewi (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Snack bars are bar-shaped products that contain carbohydrates and proteins from flour, nuts, dried fruits, and other ingredients that are processed into whole pieces and combined into one ready for consumption. Snack bar innovation with the proportion of grated coconut and tuna pindang. The purpose of this research is to meet the nutritional needs of the community by fulfilling daily protein and can be an entrepreneurial product so that it is necessary to know the organoleptic quality, nutritional content and selling price of the product. The methodology in the research is an experimental approach with quantitative analysis to fulfill the sensory quality and nutritional content of snack bars. The best proportion of snack bars with different proportions of grated coconut and pindang ikan tongkol from the sensory test was obtained from the 50:50 ratio with characteristics of rectangular shape; yellowish brown color with white spots from rengginang; grated coconut and pindang ikan tongkol aroma; crunchy texture; and taste of grated coconut and pindang ikan tongkol. Laboratory analysis of the nutritional content of the best snack bar per 100 grams contained 17.15% protein, 11.55% water content, 1.05% ash, 3.14% fat, 284.10kcal/100g energy, 64.72% carbohydrate, and 2.42% crude fiber. The selling price of snack bars with the proportion of grated coconut and tuna pindang with a percs weight of 15 grams is known to be IDR 3,000.